Perceived corporate social responsibility performance in professional football and its impact on fan-based patronage intentions: An example from Chinese football. Issue 2 (7th May 2019) - Liu, Dongfeng; Wilson, Rob; Plumley, Daniel; Chen, Xiaofeng
Abstract : Purpose: The purpose of this paper is to analyze fans' perceptions of the corporate social responsibility (CSR) activities of a professional football club, specifically whether or not perceived CSR performances are then likely to influence patronage intentions of the fans in relation to the football club. Design/methodology/approach: The paper uses the example of a professional football club in China as a case study for data analysis. Based on a sample of 451 home team fans, analysis was conducted through calculation of descriptive statistics, and exploratory factor analysis. Regression analysis was conducted to determine the impact of perceived CSR performance on fans' patronage intentions. Findings: The results revealed that factor 3 ("CSR to customer and employee") and factor 4 ("Community development and youth education") were significantly predictive of all the three patronage intention variables, i.e. repeat purchase, word-of-mouth and merchandise consumption. In addition, factor 2 ("charity") would also affect merchandise consumption intention, but have no effect on any other dimensions. Originality/value: A scale measuring perceived CSR performance in professional football clubs by the fans in the Chinese context has been developed. In addition, the authors have identified that the two main CSR factors that would influence fans' patronage intentions are: "CSR to the customer and employee" and "community development and youth education." Thus, if football clubs are to use CSR strategically to leverage spend, then it is these two areas that they should focus on, explicitly in relation to CSR activities. This paper adds value to an area that is currently under-researched in respect of CSR activities in Chinese professional football.